Pengaruh Pemberian Kompos Ampas Tebu (Saccharum officinarum L.) dan Daun Lamtoro (Leucaena leucocephala) Terhadap Pertumbuhan dan Hasil Kedelai (Glycine max L.) - Prasapna, Mardyana; Ananto, Ananto; Sari, Wilna; Putri, Santi Diana (UNIVERSITAS LABUHANBATU, 2024)
Research on the effect of giving sugarcane bagasse compost (Saccharum officinarum L.) and lamtoro leaves (Leucaena leucocephala) on the growth and yield of soybean plants (Glycine max L.) was carried out in the experimental garden of the Agroindustry Departement, Padang State University, Sijunjung campus from August to December 2021. This research was arranged based on a Randomized Block Design (RAK) with two factors. The first factor is the dose of sugarcane bagasse compost (A0: 0 kg/polybag, A1: 160 g/polybag, A2: 320 g/polybag, A3: 480 g/polybag), the second factor is the dose of lamtoro leaf compost (B0: 0 g/polybag, B1: 60 g/polybag, B2: 120 g/polybag). The purpose of this study was to determine the effect of a combination of bagasse compost and lamtoro leaves on the growth and yield of soybean plants and to obtain the dose of bagasse compost and lamtoro leaves on the growth and yield of soybean plants. The study was analyzed using the F test at the 5% level and if the calculated F value> F table 5%, then continued with the Duncans New Multiple Range Test (DNMRT) at the 5% level. The parameters observed were plant height, number of leaves, number of stems, the first flower appeared and the weight of 100 pods per plant. Based on the results of the study of the provision of bagasse compost and lamtoro leaves on the growth and yield of soybean plants that have been carried out, it can be concluded that the provision of a combination of bagasse compost and lamtoro leaves compost has a different effect that is not significant on all treatment parameters. Keywords: sugar cane compost, lamtoro leaf compost, soybean